Efektivitas Hypnobreastfeeding terhadap Peningkatan Produksi ASI - Rosa, Eni Folendra; Suryanda, Suryanda; Ruastiati, Nelly; Salsabillah, Dea (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Ineffective breastfeeding is a condition where the mother and baby experience dissatisfaction or difficulty in breastfeeding. Milk production depends on physiological and psychosocial factors. Nursing interventions that can be given are breastfeeding education and hypnobreastfeeding. This study aims to find out the description of breastfeeding education and hypnobreastfeeding for mothers who experience inadequate milk production. This study uses a case study method with a nursing process approach to clients with inadequate milk production. The subjects in this case study were 2 breastfeeding mothers who were in the Tanjung Agung Health Center area. The research data was taken using interviews, observation and documentation studies. Analysis and presentation of data is a description of the research results with reference to the research focus. The results of this study indicate that the application of breastfeeding education and hypnobreastfeeding can be used as a way to help smooth the breastfeeding process. The researchers concluded that hypnobreastfeeding was effective in increasing milk production, as evidenced by the frequency of breastfeeding and increased frequency of urination. The research is expected to be an input for health workers, especially nurses, to improve health education for breastfeeding mothers to implement hypnobreastfeeding.